Tax Avoidance Pada Perusahaan Manufaktur Ditinjau Dari Profitabilitas, Pertumbuhan Penjualan, Leverage, dan Komite Audit - Gde Herry Sugiarto Asana (Juara: Jurnal Riset Akuntansi, 2021)
Tax is one of the obligations that must be fulfilled by the taxpayer. This condition will lead the taxpayers to do tax avoidance. Tax Avoidance is an action to reduce taxable profits through tax planning in order to obtain a low tax expense. The purpose of this research is to examine the impact of profitability, sales growth, leverage, and audit committee on tax avoidance which is measured using effective tax rates on manufacturing companies listed on Indonesian Stock Exchange for the period of 2016 to 2018. The population in this research are all manufacturing companies listed on Indonesian Stock Exchange (IDX) during the period of 2016-2018. The sampling technique in this research used a purposive sampling method and obtained 32 manufacturing companies. The analysis technique in this research used multiple linear regression analysis techniques. The results of this research concluded that profitability (ROA) had a positive impact on tax avoidance, sales growth had a positive impact on tax avoidance, leverage as measured by DER had a positive impact on tax avoidance, while the audit committee had a negative impact on tax avoidance. The coefficient of determination in this research amounted to 0.855 which means that the tax avoidance variable is impacted by 85.5% by the variables in this research, the rest is impacted by other variables outside this research.